ANALISIS PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL MELALUI PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERASI - Solikah, Tutut; Riyanto, Wahyu Hidayat; Sari, Novi Primita (Program Studi Ekonomi Pembangunan, 2024)
This research aims to analyze the influence of Regional Original Income and General Allocation Funds on Capital Expenditures through Economic Growth as a moderating variable in Regencies/Cities in East Java Province in 2013-2022. The type of research used in this research is quantitative and the data used is secondary data. The data used was obtained from the Central Statistics Agency (BPS). This research uses panel data regression techniques with moderating variables (Moderating Regression Analysis) using the Eviesw program. The results of this research show that Regional Original Income has a negative and significant impact on capital expenditure and the General Allocation Fund has a positive and significant impact on capital expenditure. And Economic Growth was not able to moderate Regional Original Income towards Capital Expenditures with negative and insignificant results but Economic Growth was able to moderate the General Allocation Fund towards Capital Expenditures in East Java Province with positive and significant results.